2015
DOI: 10.1055/s-0034-1398985
|View full text |Cite
|
Sign up to set email alerts
|

Strain Elastography Evaluation of Rectal Tumors: Inter- and Intraobserver Reproducibility

Abstract: Visual evaluation of elastography loops is highly reproducible in an offline setting with blinded observers, and correlates significantly with pT-stages. Strain elastography performs better than ERUS and might consequently improve staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
(11 reference statements)
0
17
0
2
Order By: Relevance
“…Amended versions of this visual score have been proposed for other organs, such as for the pancreas and lymph nodes by EUS elastography. Both the continuous visual analog scale (VAS) score and categorical visual scores for endoscopic assessment of rectal tumors has shown comparable results with SR measurements [23]. In a comparative study of SR and the five-point visual elastography breast scale, SR was more accurate.…”
Section: Discussionmentioning
confidence: 98%
“…Amended versions of this visual score have been proposed for other organs, such as for the pancreas and lymph nodes by EUS elastography. Both the continuous visual analog scale (VAS) score and categorical visual scores for endoscopic assessment of rectal tumors has shown comparable results with SR measurements [23]. In a comparative study of SR and the five-point visual elastography breast scale, SR was more accurate.…”
Section: Discussionmentioning
confidence: 98%
“…Also, we did not perform an interobserver and intraobserver study of the patients. However, Waage et al 25 have recently reported that rectal elastography is highly reproducible. At present, endorectal shear wave measurement is only available from one vendor, and with ERUS ARFI technique, it would also be possible to measure the elasticity of tumours .10 cm above the anal verge.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Regarding endorectal elastography, there are still not enough studies to make firm statements. For now, the results are very promising in this regard [49].…”
Section: Gray Scale Us (2d 3d)mentioning
confidence: 87%